The Construction of Digital Da'wah of Nahdlatul Ulama on the Playlist of "Basic Tajweed Science" Youtube NU Online: An Analysis of Norman Fairclough's Critical Discourse - Yoga Dwi Prada (Journal of Nahdlatul Ulama Studies, 2026)
This study examines the construction of Nahdlatul Ulama's digital da'wah in the Basic Tajweed Science playlist on the NU Online YouTube channel. As digital media increasingly reshape religious communication, this study analyzes how NU Online constructs Nahdlatul Ulama's religious authority through digital tajweed learning and its implications for Islamic moderation and digital religious literacy. Previous studies have mainly examined digital da'wah in terms of communication strategies, audience engagement, or media effectiveness, while limited attention has been given to digital tajweed learning as a discursive site for constructing Nahdlatul Ulama's religious authority and moderate Islamic identity. A qualitative approach was employed using Norman Fairclough's Critical Discourse Analysis (CDA) as the primary analytical framework, complemented by Kress and van Leeuwen's multimodal analysis to examine visual and textual representations within the textual dimension of the CDA framework. The data consisted of four purposively selected videos from the playlist and were collected through documentation and non-participant observation, supported by relevant literature. The findings indicate that NU Online employs contextual language, persuasive rhetoric, and multimodal visual strategies to simplify classical tajweed concepts for digital audiences. The analysis also indicates that religious authority is represented through references to pesantren scholarly traditions, sanad-based explanations, systematic instructional sequencing, and platform-oriented presentation, including accessible language and concise video organization. At the socio cultural level, these discursive practices can be interpreted as supporting Nahdlatul Ulama's religious authority while providing discursive resources for Islamic moderation and digital religious literacy. The novelty of this study lies in integrating Fairclough's CDA with multimodal analysis to examine digital tajweed learning as an institutional digital da'wah practice.